Self-compassion as mediator between self-critical perfectionism and depressive symptoms among Malaysian university students. - Xin, Leo Jia; Wan Jaafar, Wan Marzuki (Human Resources Management Academic Research Society (HRMARS), 2024)
In Malaysia, exacerbated by the COVID-19 pandemic, mental health concerns have surged, with a Ministry of Health report predicting that mental illness will affect one-third of the population. Prior studies indicate a substantial range of depressive symptoms among Malaysian university students, ranging from 30% to 64.2%. Moreover, more than 75% of individuals with mental illnesses remain untreated, highlighting a critical research gap and the urgency for tailored interventions, especially given the rising number of suicide ideation and attempts among Malaysian youth. Despite the acknowledged significance of self-critical perfectionism and self-compassion in determining depressive symptoms, prior research has predominantly focused on Western populations, necessitating a culturally nuanced investigation. Thus, this study aims to address this gap by exploring the relationship between self-compassion, self-critical perfectionism, and depressive symptoms among Malaysian university students. A descriptive and correlational research design, employing a convenience sampling method, was utilized for data collection involving 518 Malaysian university students aged 18 to 29. A structured self-administered questionnaire, comprising the Self-Compassion Scale (Neff, 2003b), Almost Perfect Scale-Revised (Slaney et al., 2001), and Patient Health Questionnaire-9 (Kroenke et al., 2001), was employed. Analysis using the Statistical Package for Social Science (SPSS) revealed a substantial prevalence of depressive symptoms (64.5%) at a moderately average level, emphasizing the need for urgent intervention. The majority exhibited self-critical perfectionism (81.7%), while self-compassion was at a moderate level (71.2%). Significant negative relationships were found between self-compassion and selfcritical perfectionism with depressive symptoms, contrasting with a significant positive relationship between self-critical perfectionism and depressive symptoms. The study further established that both self-compassion and self-critical perfectionism significantly predict depressive symptoms. In addition, noteworthy mean differences between undergraduates and postgraduates emerged in depressive symptoms through t-test analysis. Therefore, the program of study was controlled while conducting the mediation analysis of self-compassion between the variables. In conclusion, this study contributes significantly to the understanding of a model suggesting the partial mediating role of self-compassion between self-critical perfectionism and depressive symptoms among university students. These findings advocate for targeted interventions and a supportive environment for students' psychological wellbeing.